Adsorptive Thermochemical Energy Storage and it’s Impacts on Space Heating - Worboy, Griffin (Université d'Ottawa | University of Ottawa, 2024)
Over the past 200 years, human activities have increased the carbon dioxide content in the atmosphere by 50% [1]. Currently, this corresponds to a 1.1oC rise above 1850-1900 average global temperatures in 2011-2020 [2]. If the global average temperature continues to rise past 1.5oC, the human population will face unprecedented climate-related risks and weather events [3]. In 2020, over half (53.5%) of the energy consumed by the space heating sector in Canada was supplied by fossil fuels [4]. To help reduce fossil fuel emissions and reach 2050 net zero goals a reduction in greenhouse gas emissions is required. To help address the problem, a heat storage technology is developed to store thermal energy for use in space heating applications. The focus on this thesis is on the modelling and simulation of the thermal energy storage technology developed based on exothermic adsorption process and its validation with experimental results. The effect of column volume and length to diameter ratios on the performance of the system have been experimentally studied and simulated. The simulation was carried out by using gPROMS (general Process Modelling System) software. It incorporates single dimension heat and mass transfer equations where the radial changes along the column are neglected. The simulation uses the Guggenheim-Anderson-de Boer (GAB) isotherm model to describe the moisture equilibrium behaviour with the adsorbent sample. The modelling results show good agreement with the experimental data. Effects of length to diameter ratios show an increasing trend in energy storage density with decreasing length to diameter ratios. The fitted model was also coded in Fortran and implemented in a TRNSYS (Transient System Simulation Tool) simulation to study the performance of this energy storage technology in home heating scenarios. Using the results from the TRNSYS simulation the economic viability of this technology is explored.
Keywords: Adsorption; Thermal Energy Storage; Modelling Adsorption Systems